Realisation of RPS from electrical home appliances in a smart home energy management system. Issue 1 (7th October 2019) - Gautam, Samir; Dah‐Chuan Lu, Dylan; Xiao, Weidong; Lu, Yuezhu
Abstract : With the increasing integration of photovoltaic power generation in the low‐voltage distribution network, the grid voltage regulation becomes critical, which demands support from different resources. This study presents the feasibility study of home appliance to be applied for appliance to grid mode of operation. The analysis includes the amendments in topology and control to support the concept of supportive platform provided by smart home and smart grid. Home appliances are then proposed as new distributed reactive sources, which are utilised to resolve the issue of voltage regulation, as well as produce reactive power locally for voltage stability. This study discusses the technical transitions in current home appliance to accommodate auxiliary functionality of grid reactive power support (RPS) and how it can fit in the home energy management system architecture to provide the required RPS.